PROPOSE STRATEGY FOR PROJECT MANAGEMENT IMPROVEMENT AT PT AKSAMAIA REKTA NUSA (The Indonesian Journal of Business Administration, 2019)
As a new consultant company, PT Aksamaia Rekta Nusa (Aksamaia) is facing the challenge of difficulties in managing the projects properly. Some recent projects experienced delays in project completion and decreased actual profit margins compare to what its planned in the beginning. This research aims to help Aksamaia to increase its project profit margin by improving the project management methodology. To improve project management for Aksamaia, it is necessary to collecting data and information to find out the existing conditions. In order to anticipates the type of data needed and the data availability, this research use qualitative research methodology. This research collected primary data by Focus Group Discussion (FGD) and unstructured interview with Aksamaia directors and employees consecutively. Current Tree Reality (CRT) was used to perform root cause analysis and found five reasonable root causes and Project Management Body of Knowledge (PMBOK) approach was used as guidelines to find the alternative solutions. Three alternative solutions have the highest percentage to improve the project management in Aksamaia based on Analytical Hierarchy Process (AHP) analysis. The first alternative is improve project cost estimation process, second, conduct a formal or informal training to improve human resource capability, and third, allocate proper budget for new equipment.Keywords:  project management, consultant company, PMBOK, CRT, AHP